Building Emotional Awareness and Mental Health (BEAM): study protocol for a hybrid implementation-effectiveness trial of the BEAM app-based program for parents with clinical mental health problems - Kaeley M. Simpson; Robert J. W. McHardy; J. Grace Zhou; Sydney Levasseur-Puhach; Cynthia M. Côté; Millie Braun; Fiona Clement; Anna L. MacKinnon; Nathan Nickel; Tracie O. Afifi; Gerald F. Giesbrecht; Ryan Giuliano; et al. (BMC Psychiatry)
Abstract Background Children are highly sensitive to adversity during their first five years of life, with exposure to chronic parental mental illness (MI) consistently linked to socio-emotional impairments and mental health problems in children. Children born during the COVID-19 pandemic were exposed to unprecedented levels of parental distress, with parental MI reported at three times the pre-pandemic rates. This situation underscored a pressing need for scalable solutions to foster positive mental health and developmental outcomes for a generation of children. In response, we developed the Building Emotional Awareness and Mental Health (BEAM) program, an innovative mobile health (mHealth) solution for parents of young children. Clinical trials to date evaluating BEAM have shown promising results, demonstrating reductions in parent depression, suicidality, anxiety, and harsh parenting practices. This trial involves an effectiveness-implementation hybrid design with co-primary aims of (1) determining BEAM’s effectiveness in improving parent mental health, and (2) evaluating the implementation of BEAM in the community through metrics such as feasibility, acceptability, and uptake. This trial’s secondary aim is to measure BEAM’s effectiveness in improving short-term child mental health and developmental outcomes using primary data and long-term psychosocial family outcomes using administrative data. A final exploratory aim of this trial will measure the cost-utility of delivering BEAM relative to extant health programming. Methods A single arm trial with repeated measures will be used to evaluate the effectiveness of implementing the BEAM intervention in the community with a sample of 400 parent participants with a child aged 24–71 months. Participants must self-report moderate to severe symptoms of depression, anxiety, parenting stress, and/or anger at time of enrolment (T0) and live in the province of Manitoba, Canada. Individuals will be recruited through four streams including the (1) Manitoba Crisis Response Services, (2) primary care offices (paediatricians and/or general practitioners), (3) Manitoba family community organizations and child care centres, and (4) social media. Study participants will complete 12 weeks of psychoeducation modules, with access to an online social support forum and check ins with a peer coach. Assessments of parent and child mental health symptoms will occur at pre-test before BEAM begins (T1), immediately after the last week of the BEAM intervention (post-test, T2), 6-month follow-up (T3), and 12-month follow-up (T4). Discussion The BEAM program offers a promising solution to address elevated parental mental health symptoms, parenting stress, and related child functioning concerns. The present implementation trial aims to extend the groundwork established by an open pilot trial and RCT of the BEAM program, in a next step of testing BEAM’s readiness for nationwide scaling. Trial registration ClinicalTrials.gov NCT06455397. Registered on June 11, 2024.